Analysis of the scientific production on social media and libraries in Information Science journals in Brazil - Franca, Maira Nani [UNESP]; Grossi de Carvalho, Angela Maria [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2019)
Social media is inserted in the much of society around the world in various segments, impacting the way of acting, thinking and relating to the subject. To libraries, as organizations responsible for providing access to information, to knowledge and learning, it is essential the monitoring of social changes and technological transformations, so they can fulfill their role in contemporary society. In this context, with this study aims to identify the characteristics of the Brazilian scientific literature regarding social media and libraries in order to monitor its evolution and point out trends. This is a descriptive study of qualitative-quantitative nature, based on the domain analysis, proposed by Hjorland. The research universe consists of 54 articles published in national scientific journals of Information Science. It was found that the analyzed domain has been discussed in the community since 2007, especially in the context of University libraries. Most authors cited belong to Information Science, in collaboration with researchers from Social Communications and Sociology. The initial stage of formation of an epistemic community in Information Science was identified. Social networks has been the terminology commonly adopted by the researchers of the area to represent the communication environments mediated by the computer, though, the term social media has been featured in recent years. New lexicons in the analyzed domain have been identified for possible update of organization and representation schemes of knowledge produced in the country, in the field of Information Science.
Keywords: Social networks; Social media; Library; Domain analysis; Scientific production